Effectiveness of Law Enforcement on Mining Crime Without Permission (PETI) in Wonosobo - Budi Raharjo (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The background of this research is the rampant mining without permission (PETI) due to the mindset of society or mining entrepreneur who is not based on the exploitation of environmental awareness that will have lasting impact on the next generation. This journal aims to analyze the effectiveness of law enforcement on mining crime without permission in Wonosobo. The method used in the form of in-depth case studies, explores and elaborates on PETI mining case. While the documents studied are the Investigation Report of PETI crime suspection in Wonosobo. The analysis is concerned with the investigation of cases of PETI facts in violation of Article 158 of the Mining Act. The results of the research community was not aware of the law related to the licensing of mining, proved the existence of dredging sand in the suspect area, but the mining business is not licensed. The author suggests the socialization of law and public law for the voluntary movement of miners, so a realization that a legal substance in the Mining Act can be used as a means of protecting the public with government and environmental sustainability.Keywords: Effectiveness; Law Enforcement; Mining Crime Without Permission.